Do menu costs make prices sticky? - Eife, Thomas A. (Discussion paper series, 2008)
This paper studies whether menu costs are large enough to explain why firms are so reluctant to change their prices. Without actually estimating menu costs, we can infer their relevance for firms' price setting decisions from observed pricing behavior around a currency changeover. At a currency changeover, firms have to reprint their price tags (menus) independently of whether or not they want to change prices. And if this is costly, firms' price setting behavior is altered in the months around the changeover. Using data from the Euro-changeover, the paper estimates that menu costs can explain a stickiness of around 30 days which is considerably less than the 7 to 24-month stickiness we observe in retailing and in the service sector. The reluctance of firms to adjust prices more frequently appears to be caused by factors other than menu costs.
Keywords: Arbeitspapier; Graue Literatur